Becoming a graphic and digital designer a guide to careers in design - Heller, Steven; Vienne,Veronique (John Wiley & Sons, 2015)
"Building on the past sucesses of Becoming a Graphic Designer and Becoming a Digital Designer, this newly combined fifth edition addresses the demands of finding and suceeding at a design career in the 21st century" -- Back cover.